Economic growth without carbon emission: Comparative perspectives on solar, wind, hydroelectric, nuclear, and geothermal energy - Rongrong Li; Qiang Wang; Sailan Hu (Energy Strategy Reviews)
As the global demand for sustainable energy intensifies, achieving economic growth without carbon emissions has become both a critical challenge and an opportunity. This study investigates the potential of five major clean energy sources—solar, wind, hydroelectric, nuclear, and geothermal energy—in fostering economic growth while reducing carbon emissions. Despite the growing interest in clean energy, the comparative effectiveness of these energy sources in different economic and environmental contexts remains underexplored, particularly concerning their nonlinear relationships with economic development and emissions. To address this gap, this study uses a robust panel dataset covering 24 countries from 2005 to 2020, and employs fixed-effect and panel threshold models to uncover the nuanced relationships between clean energy consumption, GDP, and CO2 emissions. The results indicate a positive impact of clean energy consumption on economic growth across all five energy types, with solar and wind contributing to steady development. However, the relationship with CO2 emissions varies: solar, wind, and geothermal significantly reduce emissions, while hydroelectric and nuclear energy are associated with higher emissions due to infrastructure complexities. Threshold regression analysis further identifies nonlinear effects moderated by geopolitical risk. For solar and wind energy, the carbon-reducing impact becomes more pronounced when risk levels exceed the threshold, while hydroelectric and nuclear energy show escalating emissions in high-risk environments. This study highlights solar and wind energy as the most effective solutions for achieving carbon-free economic growth, while hydroelectric and nuclear energy require improved governance and risk management frameworks to minimize their environmental trade-offs.